Effects of acupuncture on muscular strength, power, and endurance - Yeo, Qiu Han (2014)
Acupuncture is widely used to treat pain and illnesses. Recently there is growing interest in the effects of acupuncture on sports performance, but studies have shown little and conflicting results. The purpose of this study was to examine the effects of acupuncture on muscular strength, power, and endurance on young healthy individuals. Nineteen participants were randomly assigned to one of the two treatment groups: acupuncture or sham. In the acupuncture group, bilateral needling was administered at Zusanli (ST-36), Quchi (LI-11), and Yanglingquan (GB-34) for a total of eight sessions. Similar needling was administered on non-acupuncture points for sham group. Participants were asked to performed isokinetic knee extension and flexion and isometric contraction. Three measurements were taken: baseline, after first treatment, and after final treatment. Testing parameters included peak torque, work per repetition, average power per repetition, time to peak torque, total work done, and average power per repetition. The main results demonstrated 1) no interaction between treatments and sessions; 2) no difference between acupuncture and sham treatment; 3) both needling caused significant increase in isokinetic strength and power. The findings concluded no difference between acupuncture and sham treatment. However, both needling are effective in increasing muscular strength and power.